The Audience's Use of TV Channel Pages on Social Media Platforms to Increase Political Awareness (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
Research title: The audience's use of TV channel pages on social media platforms to increase political awareness. This study aims to investigate how the audience uses TV channel pages on social media platforms to increase political awareness. After the media integration between satellite channels and social media sites, these platforms have become an effective tool for disseminating information and interacting with the audience.As well as knowing the use of satellite channel pages on social media sites increases the political awareness of the audience, as well as how to analyze the impact of these pages on increasing political awareness among the audience, as well as knowing the types of political content that most influence the audience. The survey method was used, which is considered the appropriate method for studying through the questionnaire tool with a sample of followers of TV channel pages on social media platforms such as Facebook, Twitter and Instagram, where the results showed that the target audience uses TV channel pages on social media sites to obtain reliable and fast political information. These pages also contribute to increasing political awareness by providing diverse and comprehensive content. Also, interaction with political content on these pages enhances the audience's understanding of political issues.